METHODS FOR DETERMINING THE ICE-FORMING EFFICIENCY OF ANTI-HAIL PRODUCTS ON LABORATORY INSTALLATIONS - B. Khuchunaev; S. Budaev; A. K. Gekkieva (Наука. Инновации. Технологии, 2022)
Introduction. This article presents a method for determining the ice-forming efficiency of anti-hail products with an output of more than 107 active particles per 1 g of reagent at laboratory facilities of the High Mountain Geophysical Institute. The physical basis for the use of crystallizing reagents is the ability of their aerosols to create ice crystals in a supercooled cloud environment, which grow rapidly due to the distillation of water vapor from surrounding droplets, which helps to resolve the phase instability of a supercooled cloud environment [1]. One of the most widely used reagents when exposed to supercooled clouds in order to prevent hail and precipitation is silver iodide AgI. At the same time, the effectiveness of this reagent when interacting with a supercooled cloudy environment at a temperature of minus 6 °С and above decreases. In this regard, studies in the field of increasing the ice-forming efficiency of anti-hail products are quite relevant to the present time. Materials and methods of the research. A measure of the effectiveness of the ice-forming reagent is the number of active particles obtained from a unit mass of the reagent (hereinafter referred to as the yield), converted into an aerosol in one way or another, in particular, by burning a pyrotechnic composition with an ice-forming substance. The principle of measuring the effectiveness of an ice-forming reagent consists in determining the number of ice crystals formed when a known amount of the reagent under study is introduced in the form of an aerosol into a supercooled water mist. Pyrotechnic compositions used in anti-hail products such as «Alazan-6» and «Alazan-9» were considered as a working material for laboratory research [2, 3, 4]. The results of the study and their discussion. The article presents a method for determining the ice-forming efficiency of anti-hail products at laboratory facilities of the High Mountain Geophysical Institute. The use of this method will increase the ice-forming eficiency of anti-hail products using various additives to the pyrotechnic composition. Conclusions. The method presented in this article can be used by research institutions, Keywords: paramilitary services of active influence and other organizations of the Federal Service for Hydrometeorology and Environmental Monitoring, which develop, introduce and test new ice-forming reagents and pyrotechnic compositions.